Role of Transforming Growth Factor-β1 and Smads Signaling Pathway in Intrauterine Adhesion - Umme Salma; Min Xue; Md Sayed Ali Sheikh; Xiaoming Guan; Bin Xu; Aiqian Zhang; Lihua Huang; Dabao Xu (Hindawi Limited, 2016)
The aim of the study was to evaluate the role of Smad3, Smad7, and TGF-β1 in intrauterine adhesion (IUA) patients and experimental rabbit models. 60 IUA patients, 30 control participants, and 18 female rabbits were enrolled in this study. We found that the plasma concentrations and protein expressions of TGF-β1 were significantly increased in patients and experimental rabbits compared to those in controls (P<0.05). Furthermore, the mRNA and protein expression levels of Smad3 were significantly elevated, while Smad7 level was markedly decreased in the patients and experimental rabbits compared with controls (P<0.05). This altered ratio recommended that IUA was positively correlated to the mRNA and protein expression levels of Smad3, Smad7, and TGF-β1 in blood and uterine tissue. Moreover, we used the specific inhibitor of Smad3 (SIS3) in experimental rabbit. SIS3 obviously reduced the mRNA and protein expression of smad3 and TGF-β1, while it increased Smad7 expression in the treatment groups as compared with IUA rabbits (P<0.05). Our study suggested that TGF-β1/Smad3/smad7 is a major pathway which plays an important role in the regulation of the IUA and specific inhibitor of Smad3 (SIS3) may provide a new therapeutic strategy for IUA.